2009
DOI: 10.1590/s1808-86942009000400014
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory alteration evaluation in patients with chronic otitis media

Abstract: Many studies have shown the consequent gustatory alteration caused by ear surgeries. However, few have reported this alteration in patients with chronic otitis media (COM), prior to surgical treatment. Aim: to identify gustatory alterations due to chorda tympani nerve involvement in patients with COM without prior surgery. Methods: Clinical essay, with tests based on "taste strips" with different concentrations of salt, sweet, bitter, and sour, was performed in 45 patients with unilateral cholesteatomatous or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…In our study, there were no significant differences among the 4 taste qualities. Landis et al (6) and Felix et al (7) also reported that filter paper taste strips detected significant differences between each taste type. However, we found that CTN damage did not cause significant differences among the 4 taste qualities.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our study, there were no significant differences among the 4 taste qualities. Landis et al (6) and Felix et al (7) also reported that filter paper taste strips detected significant differences between each taste type. However, we found that CTN damage did not cause significant differences among the 4 taste qualities.…”
Section: Discussionmentioning
confidence: 96%
“…Sano et al (8) reported that the EGM thresholds of patients with COM and cholesteatoma were significantly higher than those of patients with otosclerosis. Landis et al (6) and Felix et al (7) studied taste function in patients with chronic inflammatory middle ear diseases using filter paper taste strips and concluded that chronic inflammatory middle ear diseases affect taste function. Furthermore, they reported that the mean taste scores were significantly higher on the healthy side than on the affected side in patients with COM and cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The Journal of Laryngology & Otology of the patients and the duration of the disease with the preoperative or post-operative taste score in both groups in any of the follow-up periods, as described by Goyal et al 12 In contrast, Felix et al concluded that the duration of the disease and the pre-operative morbidities adversely affect the gustatory outcome of a patient with otitis media. 20 As described by Sone et al, the chance of recovery for younger patients is better than for older patients. 21 When gustatory scores were compared in patients with and without the preservation of the chorda tympani nerve in mucosal disease, we did not find any significant difference in improvement between the two groups.…”
Section: Discussionmentioning
confidence: 96%
“…concluded that the duration of the disease and the pre-operative morbidities adversely affect the gustatory outcome of a patient with otitis media. 20 As described by Sone et al ., the chance of recovery for younger patients is better than for older patients. 21 When gustatory scores were compared in patients with and without the preservation of the chorda tympani nerve in mucosal disease, we did not find any significant difference in improvement between the two groups.…”
Section: Discussionmentioning
confidence: 98%